2016
DOI: 10.1093/humrep/dew309
|View full text |Cite
|
Sign up to set email alerts
|

Natural conception: repeated predictions over time

Abstract: This study was facilitated by grant 945/12/002 from ZonMW, The Netherlands Organization for Health Research and Development, The Hague, The Netherlands. No competing interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…We defined subfertility as not conceiving within 1 year of trying. Unexplained subfertility was defined as couples with no major causes explaining the fertility problem, regular menstrual cycles of length between 23 and 35 days, at least one patent fallopian tube and semen analyses with a total motile sperm count of >1 × 10 6 ( van Eekelen et al , 2017a ). We chose 38 years as the age limit for women as for couples in which the woman over 38 years of age, the treatment choice is complicated by the rapid decline in the probability of live birth after IVF and after EM as female age increases, such that IVF-EM-EM might be preferred ( McLernon et al , 2016 ; van Eekelen et al , 2019b ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We defined subfertility as not conceiving within 1 year of trying. Unexplained subfertility was defined as couples with no major causes explaining the fertility problem, regular menstrual cycles of length between 23 and 35 days, at least one patent fallopian tube and semen analyses with a total motile sperm count of >1 × 10 6 ( van Eekelen et al , 2017a ). We chose 38 years as the age limit for women as for couples in which the woman over 38 years of age, the treatment choice is complicated by the rapid decline in the probability of live birth after IVF and after EM as female age increases, such that IVF-EM-EM might be preferred ( McLernon et al , 2016 ; van Eekelen et al , 2019b ).…”
Section: Methodsmentioning
confidence: 99%
“…As the baseline probability of live birth after EM in the model, we chose to use our dynamic prediction model for natural conception ( van Eekelen et al , 2017a ). This prediction model has been externally validated in Scottish data and can be used to not only predict the probability of natural conception after completion of the fertility workup that leads to ongoing pregnancy, but also to update predictions when couples return to the clinic later after a period of EM ( van Eekelen et al , 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that allostatic load that is specific in chronic situation like infertility was not associated with fertility outcomes like conception, spontaneous abortion, and live birth (16). However, a cohort study on 4,999 couples showed that the prediction ranges could help in counselling couples for at least two years after their fertility work-up (17). Additionally, a longitudinal cohort study showed a 71.6% live birth after ART and 28% after SPs or both up to five years (18).…”
Section: Discussionmentioning
confidence: 99%
“…Traditional logistic regression would not be able to utilise such patient information as it violates the independence assumption, that each observation (for an individual) is independent of other observations. An alternative model to handle cycles of patient information is a beta-geometric model that has been used to predict natural conception for women, after multiple cycles of a relevant procedure [31]. Time-varying effects [25], time-since-measurement as a predictor [27], aggregated covariate [26].…”
Section: Generalised Estimating Equationsmentioning
confidence: 99%